Fatty Liver Disease in Persons With HIV Infection - Seth, Aradhna (Top Antivir Med, 2019)
The leading cause of non-HIV-related mortality is liver disease. Fatty liver disease can be characterized as alcoholic or nonalcoholic in nature. Alcohol use is prevalent among individuals with HIV infection and can lead to medication nonadherence, lower CD4+ cell count, inadequate viral suppression, and disease progression. The pathogenesis of nonalcoholic fatty liver disease (NAFLD) in individuals with HIV infection includes metabolic syndrome, hyperuricemia, HIV-related lipodystrophy, genetic polymorphisms, medications, HIV itself, and the gut microbiome. The prevalence of NAFLD in persons with HIV infection ranges from 30% to 65% depending on the modality of diagnosis. Individuals with HIV infection and NAFLD are at higher risk of cardiovascular disease; however, there is a dearth of longitudinal outcomes studies on this topic. Current therapies for NAFLD, such as vitamin E and pioglitazone, have not been studied in persons with HIV infection. There are several drugs in phase II and III clinical trials that specifically target NAFLD in HIV, including CC chemokine receptor 5 inhibitors, growth hormone-releasing factor agonists, and stearoyl-CoA desaturase inhibitors. Persons with HIV should be screened for NAFLD while pursuing aggressive risk factor modification and lifestyle changes, given the increased risk of cardiovascular mortality.